Income Analysis of Tomato Farming in Paddy Fields in Leuntolu Village Raimanuk District Belu Regency - Yasinhta Bete; Umbu Joka; Agustinus Nubatonis (Agribusiness Journal, 2021)
This study aims to know (1).  To know how much the income from tomatoes farming in Leuntolu Village, Raimanuk District, Belu Regency , (2)  To know the relative advantages of tomatoes farming in Leuntolu Village, Raimanuk District, Belu Regency.  The research was conducted in August 2020. Techniques of data collection using survey methods with primary data and secondary data. The sample used in this study was 30 respondents. The data analysis method used in this research is descriptive qualitative analysis method, income analysis and R / C ratio. The results showed that: the tomatoes farming carried out had several stages including: land processing, seed selection, seed nursery, planting, maintenance (watering, fertilizing and weeding), harvest and post-harvest. The results of tomato farming research with a total revenue in 2018 of Rp. 153,540,000 divided by the total cost of Rp. 73,517,763.00, it will get a relative profit of 2.09 so that tomatoes farming in Leuntolu Village, Raimanuk District, Belu Regency is profitable / provides benefits to farmers in Leuntolu Village